The effect of the spatial resolution of NDVI-Ts spaces on the evaporative fraction calculation. - Daniela Girolimetto; Virginia Venturini; Leticia Rodríguez (Tecnología y ciencias del agua, 2011)
This paper analyzes the effect of the spatial resolution of the images used to generate the Normalized Difference Vegetation Index (NDVI)-surface temperature (Ts) space. This is widely used to monitor environmental variables such as evapotranspiration (ET) and evaporative fraction (FE). The method proposed by Jiang and Islam (2001) was selected to study the effect of the spatial resolution on the calculation of the FE. For this, spatial resolutions were analyzed ranging from 1 x 1 km (common for thermal sensor images) to 10 x 10 km (consistent with images from passive microwave sensors (MP)). The results suggest that the NDVI-Ts triangular space allows for obtaining reasonably accurate FE values with low spatial resolution, such as that of MP, provided that the cold edge can be determined using images with 1 x 1 km spatial resolution. If it is not possible to calculate the cold edge with images of 1 x 1 km resolution, the results would be uncertain and, therefore, should be carefully analyzed.